Numerical solutions of fractional differential equations of Lane-Emden type by an accurate technique - Akgul, Ali; İnç, Mustafa; Karatas, Esra; Baleanu, Dumitru (Springer International Publishing Ag, 2015)
In this work, we study the fractional order Lane-Emden differential equations by using the reproducing kernel method. The exact solution is shown in the form of a series in the reproducing kernel Hilbert space. Some numerical examples are given in order to demonstrate the accuracy of the present method. The results obtained from the method are compared with the exact solutions and another method. The obtained numerical results are better than the ones provided by the collocation method. Results of numerical examples show that the presented method is simple, effective, and easy to use.
Keywords: reproducing kernel method; fractional differential equations; Lane-Emden differential equations